Exploring marine biodiversity through inquiry with elementary school students: a successful journey? - Jesus-Leibovitz, Luísa (2021)
In this work, we present a marine ecology inquiry-based activity, implemented with 164 primary school students. The main goal was to evaluate the activity’s impact on students’ understanding about biodiversity and scientific procedures. We also aimed to analyse the potential use of personal meaning maps (PMMs) to assess the impact of the activity on students’ ideas about the topics explored. The results revealed that fieldwork and the exploration of real data were the aspects most emphasised by all intervenient. Finally, the PMMs proved to be a good tool to evaluate the impact of activities developed outside classroom, with primary school levels.